Morphological Changes in Roselle’s Breeding (Hibiscus sabdariffa L) With The Provision of Manure on Ultisol Soil - Gribaldi, Gribaldi; Nurlaili, Nurlaili (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2015)
Roeselle plant (Hibiscus sabdariffa L.) are now widely cultivated, so that the need of roselle?s seed are increasing. Growing media largely determines the growth of seedlings, the use of Ultisol soil as growing media showed lower seedling growth. The efforts to overcome this can be done with the addition of manure. This study aims to determine the morphological changes of roselle seeds with the provision of manure on Ultisol soil in Polybag. This study used a completely nonfactorial randomized design with four treatments and five replications. The treatment under study consists of: P0 = without manure, P1 = cow manure, P2 = goat manure, and P3 = chicken manure. The result of this study showed the provision of manure on the planting medium affects the growth of roselle seeds in Polybag. The best seedling growth was obtained in growing media with the provision of chicken manure.